Meta-analysis with systematic review to synthesize associations between oral health related quality of life and anxiety and depression - Zainab Alimoradi; Elahe jafari; Zahra Roshandel; Marc N. Potenza; Chung-Ying Lin; Amir H. Pakpour (BDJ Open, 2024)
Abstract Objectives The present systematic review aimed to investigate how oral health related quality of life (OHQOL) associates with anxiety and depression. The study protocol was registered prospectively in the PROSPERO database (CRD42023389372). Materials and methods Studies investigating associations between OHQOL and depression and/or anxiety were included. Fisher’s Z scores were used to summarize associations between OHQOL and depression/anxiety. Funnel plots and Begg’s Tests were used to assess publication bias. Meta-regression was conducted to examine potential moderator effects in the associations. Academic databases including the ISI Web of Knowledge, Scopus, ProQuest and PubMed were systematically searched. The quality of included studies was checked with the Newcastle Ottawa Scale (NOS). Results All 15 included studies were cross-sectional (14,419 participants from nine countries; mean age=43.74 years). The pooled estimates showed weak associations between OHQOL and depression (Fisher’s z-score of 0.26 [95% CI = 0.17, 0.35; I2 = 96.2%; τ2 = 0.03]) and anxiety (Fisher’s z-score of 0.22 [95% CI = 0.001, 0.43; I2 = 97.9%; τ2 = 0.06]). No severe problems in methodology quality, publication biases, or moderator effects were observed. Conclusion Both depression and anxiety were weakly associated with individuals’ OHQOL. Although the synthesized associations were not strong, they were significant, indicating that depression and anxiety are potential factors influencing individuals’ OHQOL.